Pemanfaatan Daun Gandarusa sebagai Pencahar Alami: Edukasi dan Pembuatan Kapsul Herbal bagi Masyarakat - Alviolina, Desi; Dalimunthe, Nur'aini; Juliana (Jurnal Masyarakat Indonesia (Jumas), 2025)
Gandarusa leaves contain alkaloids, flavonoids, saponins, and steroids, which have a laxative effect. Capsules can mask the unpleasant taste of drugs and serve to preserve the active ingredients. The purpose of this study was to determine whether the ethanol extract capsule preparation of gandarusa leaves is a laxative, to determine whether the extract meets the requirements for capsule evaluation tests, and to determine the effectiveness of the ethanol extract capsule preparation of gandarusa leaves in mice. This study used an experimental method by creating a capsule formulation by adding the active ingredient from gandarusa leaves. The results obtained from the effectiveness test of gandarusa leaf ethanol extract capsules as a laxative were for formulation 3, with a 9% concentration of gandarusa leaf ethanol extract. The conclusion from this counseling was that formula 3 significantly outperformed formulas 1 and 2.